Nanocellulose: Production and Processing for Biomedical Applications. Issue 12 (26th October 2021) - Brenes, Ricardo Gonzalo Ramírez; Grieco, Maria Angela Bernardes; Bojorge, Ninoska; Pereira, Nei
Abstract: Nanocellulose (NC) is a unique and promising natural material derived from native cellulose. It has attracted much attention for its versatility in construction composites, which have improved chemical and mechanical properties. This review covers the type of biomass used and NC production methods, emphasizing biotechnological routes, which promote their biological properties (biocompatibility, biodegradability and low toxicity), fundamental for medical applications. NC has many hydroxyl groups on its surface, enabling its structure to be modifiable, adaptable and viable for various fields. Furthermore, NC‐based biosensors are suitable for food quality control, monitoring environmental analytes, and particularly in health diagnostics, such as COVID19 detection. The developed analytical devices were described in a table, including information about the sensor molecule, reading system, analyte, range, detection limit, sensitivity and analytical performance. Abstract : Nanocellulose (NC) attracts the attention of interdisciplinary researchers due to its biocompatibility, biodegradability, and unique properties. New functional materials with a wide range of pharmaceutical and biomedical applications are emerging. This work also discusses the role of cellulase in NC biosynthesis, and its integration into the biorefinery concept and production methods.